DEVELOPMENT OF ACCOUNTING INFORMATION SYSTEM BASED ON BUSINESS PROCESS MODELLING AND NOTATION AND WEB-BASED FINANCIAL REPORT FOR MSMEs - Nur Indah Riwajanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Malang is a tourist city that has natural beauty and various culinary tours, including Coffee Shops. The purpose of this paper is to evaluate an Accounting Information System (AIS) for SME stakeholders, particularly the food and beverage sector, and to design an SME AIS, in particular the revenue and expenditure processes based on Business Process Modelling and Notation (BPMN). This study adopts Research and Development approach with a case study method in four coffee shops in Malang. The results of the evaluation show that there are still shortcomings and weaknesses in the acceptance and expenditure process. To reduce such cases and improve SME operations, a BPMN-based AIS has been developed, specifically in four business processes, namely Ordering, Purchase of Raw Materials, Payroll and Balance Sheet Summary, equipped with documents to monitor business developments and prepare profits. / loss report. Prior to implementation, material experts and media experts conducted validation tests, with the results that the AIS was feasible to be implemented. In addition, the new system was piloted in two coffee shops for one month. Implementation results suggest that a BPMN-based AIS should be built to reduce these problems and improve the operations of small businesses. This would include four business processes, including ordering, purchasing raw materials, payroll, and preparing financial statements, which would be accompanied by documents and a website, https://rekapyuks.xyz, to keep track of business changes and compile a Profit/Loss Report. Prior to implementation, two experts performed validation tests, which revealed that the AIS could be implemented. Furthermore, the new system and website were tested for a month in two coffee shops. According to the study's findings, MSMEs should improve internal control to reduce fraudulent actions by segregating duties and utilizing information technology to create a web-based Profit/Loss Report.